The Relationship Between Clean And Healthy Lifesytle To Leptospirosis Incident In The Working Area Of Puskesmas Ngrayun District Ponorogo - Firdaus, Annisa (2016)
Background : Clean and healthy lifestyle is indicator of health related to infectious disease. Many people not care how to do good healthy and clean lifestyle, especially people living in rural area majority have bad clean and heathy lifestyle will have a high risk of infectious disease, such as Leptospirosis. In this case, the clean and healthy lifestyle have a relationship transmission in the incidence of Leptospirosis. Purpose of the Research : Purpose of the research is to analyze relationship between clean and healthy lifestyle to Leptospirosis incident in the working area of Puskesmas Ngrayun district Ponorogo. Methode : The design of the research is a analytic observational research by employing case control approach. The sample of the research is some people patient with Leptospirosis live in the working area of Puskesmas Ngrayun, district Ponorogo by using non random sampling technique. The amount sample were 80 respondent. The data were analyzed by using chi- square test or alternative Fisher. Objective : The objective of research is analyzed relationship between clean and healthy lifestyle to Leptospirosis incident in the working are of Puskesmas Ngrayun district Ponorogo. Results : The result of relationship between clean and healthy lifestyle to Leptospirosis is a mean good clean and healthy lifestyle 47.5% and bad clean and healthy lifestyle 52.5%, so that it can be concluded that mean bad clean and healthy lifestyle more higher than good clean and healthy lifestyle. The p- value(sig) of 0.000 met normal criteria, namely p<0.05 and (OR= 12,000, 95%Cl= 4,180-34,454) that the research found significant relationship. Conclusion: There is a relationship between clean and healthy lifestyle to Leptospirosis incident in the working area of Puskesmas Ngrayun district Ponorogo.